High levels of adiponectin attenuate the detrimental association of adiposity with insulin resistance in adolescents - Agostinis-Sobrinho, César (2020)
Background and aim: This study aimed to: i) examine the differences in insulin resistance (IR) across adiposity levels; and ii) ascertain whether high levels of adiponectin attenuate the detrimental association of adiposity with IR in adolescents.Methods and results: A total of 529 adolescents aged 12-18 years participated in this cross-sectional study (267 girls). Anthropometry and body adiposity parameters [body mass index (BMI), sum of skinfolds, body fat percentage (BF %) by bio-impedance analysis and waist circumference (WC)], were measured according to standardized procedures and categorized into age- and sex-specific quartiles. Socioeconomic status, pubertal stage and lifestyle determinants (Mediterranean diet adherence and cardiorespiratory fitness) were gathered and used as confounders. Serum adiponectin and IR (homeostasis model assessment of insulin resistance [HOMA-IR] estimated from fasting serum insulin and glucose were assessed. Analysis of covariance (ANCOVA) showed that HOMA-IR increased in a linear fashion throughout the quartiles of all adiposity measures (p < 0.001 for all), independently of age, sex, pubertal stage, socioeconomic status, adherence to the Mediterranean diet and cardiorespiratory fitness. Two-way ANCOVA showed that adolescents in the higher quartile of adiposity for BF%, BMI, WC and skinfolds sum (Q4) presented the highest adiponectin levels, and had 0.77 Standard Deviation (SD), 0.8 SD, 0.85 SD and 0.8 SD lower HOMA-IR, respectively (p < 0.01) than their low adiponectin group counterparts, after adjustments for potential confounders.Conclusion: Higher adiponectin levels may attenuate the detrimental association between adiposity and IR, particularly in subjects with higher adiposity. (C) 2020 The Italian Society of Diabetology, the Italian Society for the Study of Atherosclerosis, the Italian Society of Human Nutrition, and the Department of Clinical Medicine and Surgery, Federico II University.